Concept of Bee-Eyes Array of Fresnel Lenses as a Solar Photovoltaic Concentrator System - Chiromawa, Nura Liman; Ibrahim, Kamarulazizi (Hindawi Publishing Corporation, 2015)
This paper presents a proposal of a new configuration of an optical concentrator for photovoltaic application which may enhance the efficiency of solar cells. Bee-eyes array Fresnel lenses concentrator proposed here provide high concentration factor which is greater than1000x at the 20th zone. In addition, the system also provides room for increasing the number of zones to achieve the high concentration factor if needs arise. The transmission efficiency greater than 90% has been achieved with f -number of ≥1.25. Mathematical relations derived to obtain flux distribution at the absorber plane and the transmission efficiency as well as the position of the solar cell were used in the ray tracing simulations for 6, 18, 36, 60, 90, 126, 168, 216, 270, and 330 suns concentration systems. A transmission efficiency is linearly decreasing with the increase in the number of arrays in which the transmission efficiency of 94.42% was recorded at the array of 6 suns and 74.98% at 330 suns.